Clinical research: remote magnetic navigation vs. manually controlled catheter ablation of right ventricular outflow tract arrhythmias: a retrospective study. (1st May 2018) - Shauer, Ayelet; De Vries, Lennart J; Akca, Ferdi; Palazzolo, Jorge; Shurrab, Mohammed; Lashevsky, Ilan; Tiong, Irving; Singh, Sheldon M; Newman, David; Szili-Torok, Tamas; Crystal, Eugene
Abstract: Aims: Remote magnetic navigation (RMN) is an alternative to manual catheter control (MCC) radiofrequency ablation of right ventricular outflow tract (RVOT) arrhythmias. The data to support RMN approach is limited. We aimed to investigate the clinical and procedural outcomes in a cohort of patients undergoing RVOT premature ventricular complex/ventricular tachycardia (PVCs/VT) ablation procedures using RMN vs. MCC. Methods and results: Data was collected from two centres. Eighty-nine consecutive RVOT PVCs/VT ablation procedures were performed in 75 patients; RMN: 42 procedures and MCC: 47 procedures. CARTOXP TM or CARTO3 (Biosense Webster) was used for endocardial mapping in 19/42 (45%) in RMN group and 28/47 (60%) in MCC group; EnSite TM NavX TM (St. Jude Medical) was used in the rest of the cohort. Stereotaxis platform (Stereotaxis Inc., St. Louis, MO, USA) was used for RMN approach. Procedural time was 113 ± 53 min in the RMN group and 115 ± 69 min in MCC ( P = 0.90). Total fluoroscopic time was 10.9 ± 5.8 vs. 20.5 ± 13.8 ( P < 0.05) and total ablation energy application time 7.0 ± 4.7 vs 11.9 ± 16 ( P = 0.67) accordingly. There were two complications in RMN group and five in MCC ( P = 0.43). Acute procedural success rate was 80% in RMN vs. 74% in MCC group ( P = 0.46). After a median follow-up of 25 months (interquartile range 13–34), the success rate remained 55% in the RMN group and 53% in MCC ( P = 0.96). Conclusion: Right ventricular outflow tract arrhythmia ablations were performed using half of fluoroscopic times with Stereotaxis platform RMN compared to manual approach. Acute and chronic success rates as well as complication rates were not significantly different.